AB0012 In the elderly acpa-negative ra is more prevalent than acpa-positive ra while the composition of the acpa-response appears identical. (15th June 2017) - Boeters, D; Mangnus, L; Ajeganova, S; Lindqvist, E; Svensson, B; Toes, R; Trouw, L; Huizinga, T; Berenbaum, F; Morel, J; Rantapää-Dahlqvist, S; Mil, A van der Helm-van
Abstract : Background: Rheumatoid arthritis (RA) consists of two syndromes, one autoantibody-positive and one autoantibody-negative. This multi-cohort study assessed the age of onset in relation to the presence of autoantibodies. The association with characteristics of the anti-citrullinated protein antibodies (ACPA)-response was also explored. Objectives: 1) determine the association between age of RA-onset and the presence of ACPA, rheumatoid factor (RF) and anti-carbamylated protein (anti-CarP) antibodies, 2) study if age of onset was associated with characteristics of the ACPA-response, 3) substantiate previously reported associations between age of onset and clinical characteristics. Methods: 3, 321 1987-positive RA-patients included in the Leiden-EAC, BARFOT, ESPOIR, Umeå and Lund cohorts were studied at presentation on age of onset and the presence of ACPA, RF and anti-CarP antibodies. Logistic regression analyses were performed; effect sizes were summarized in inverse-weighted meta-analyses. Within ACPA-positive RA, ACPA-level was studied in all cohorts; ACPA-isotypes, ACPA-fine-specificity and ACPA-avidity index and clinical characteristics were studied in the Leiden-EAC. Results: From the age of fifty onwards, the proportion of ACPA-negative RA-patients increased in Dutch, Swedish and French cohorts. Similar observations were done for RF and anti-CarP. The composition of the ACPA-response did not change with increasing age of onset with respect to titer, isotype distribution, fine specificity and avidity index. With increasing age of onset RA-patients smoked less often, had higher acute phase reactants and more often a sub(acute) symptom onset. Conclusions: Data of five cohorts revealed that with higher age of onset ACPA-negative RA is more frequent than ACPA-positive RA, while characteristics of ACPA-positive RA as judged by the composition of the ACPA-response appeared not age-dependent. Although more biologic studies are needed to characterize the pathogenesis of ACPA-negative polyarthritis at older age, the present data can promote personalized treatment decisions in ACPA-negative patients in daily practice. Disclosure of Interest: None declared